Social Support From the Athletic Trainer and Symptoms of Depression and Anxiety at Return to Play - Yang, Jingzhen (J Athl Train, 2014)
CONTEXT: Few empirical studies have examined social support from athletic trainers (ATs) and its buffering effect during injury recovery. OBJECTIVE: To examine the effect of social support received from ATs during injury recovery on reported symptoms of depression and anxiety at return to play among a cohort of collegiate athletes. DESIGN: Cohort study. SETTING: Two Big 10 Conference universities. PATIENTS OR OTHER PARTICIPANTS: A total of 594 injuries sustained by 387 collegiate athletes (397 injuries by 256 males, 197 injuries by 131 females) on 9 sports teams. MAIN OUTCOME MEASURE(S): Data were collected during the 2007–2011 seasons. Social support was measured using the 6-item Social Support Questionnaire. Symptoms of depression were assessed using the Center for Epidemiological Studies Depression Scale. Anxiety was measured by the State-Trait Anxiety Inventory. We used generalized estimation equation regression models to examine the effect of the social support from ATs on the odds of symptoms of depression and anxiety at return to play. RESULTS: In 84.3% (n = 501) of injury events, injured athletes received social support from ATs during their recovery. Of these, 264 (53.1%) athletes reported being very satisfied with this social support. Whether or not athletes received social support from ATs during recovery did not affect the symptoms of depression or anxiety experienced at return to play. However, compared with athletes who were dissatisfied with the social support received from ATs, athletes who were very satisfied or satisfied with this social support were 87% (95% confidence interval = 0.06, 0.30) and 70% (95% confidence interval = 0.13, 0.70) less likely to report symptoms of depression at return to play, respectively. Similar results were observed for anxiety. CONCLUSIONS: Our findings support the buffering effect of social support from ATs and have important implications for successful recovery in both the physical and psychological aspects for injured athletes.